A method for manufacturing a boron microalloyed medium chromium ferritic stainless steel
Patent Information
- Application Number
- CN202611254869.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]430型中铬铁素体不锈钢因优异的耐蚀性、导热性,且具有磁性价格低廉,广泛应用于厨卫、家电、汽车零部件,但常规430不锈钢冷板存在两大短板:一是冷轧退火后织构不理想,塑性差,在冲压、折弯等制造过程中常显示出成型性能不足,出现冲压或折弯开裂,造成产品成材率低;二是热处理或服役过程中晶界析出Cr23C6,造成晶间贫铬,耐晶间腐蚀性能差
(1)采用本发明的制造方法,在现有430生产体系基础上,无需新增核心装备,430铁素体不锈钢成型性能得到显著提升,材料延伸率提升至35%以上,r值提升至1.3以上,Δr≤0.40,深冲性能得到明显改善;
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ferritic stainless steel metallurgical rolling technology, and relates to a method for manufacturing boron microalloyed chromium ferritic stainless steel. Background Technology
[0002] 430 type medium-chromium ferritic stainless steel is widely used in kitchen and bathroom appliances, automotive parts, and other applications due to its excellent corrosion resistance, thermal conductivity, magnetic properties, and low cost. However, conventional 430 stainless steel cold-rolled sheets have two major drawbacks: First, the texture after cold rolling and annealing is not ideal, resulting in poor plasticity and often insufficient forming performance during stamping and bending processes, leading to stamping or bending cracks and low product yield. Second, chromium precipitates at grain boundaries during heat treatment or service. 23 C6 results in chromium depletion at the grain boundaries and poor resistance to intergranular corrosion.
[0003] Currently, most common improvement methods employ Ti and Nb stabilization designs, which suppress intergranular corrosion and grain growth while simultaneously improving corrosion resistance, strength, and formability. However, this significantly increases production costs. A few studies have used boron microalloying to improve the properties of medium-chromium ferritic stainless steel; however, this approach still has the following shortcomings: 1) The boron alloying smelting process has timing issues, with deoxidation and nitrogen fixation processes lagging behind. Boron readily combines with oxygen and nitrogen to form BN and B2O3 inclusions, reducing the surface quality of the cast billet and affecting the yield. 2) The reasonable control range for trace boron is not defined. If the boron content is too high, cracks are easily generated during hot and cold working; if the boron content is too low, the grain boundary segregation strengthening and texture control effects are unstable. 3) The boron-nitrogen ratio is not controlled: when the B / N ratio is low, there is insufficient free boron, making it difficult to form stable grain boundary segregation; when the B / N ratio is high, the remaining boron easily forms boride precipitation, reducing phase transformation plasticity. 4) Currently, only single-pass smelting or annealing processes are studied. A synergistic process of smelting, hot rolling, and cold rolling suitable for boron microalloyed ferritic stainless steel cold plates has not been developed. Problems such as boron element segregation control in the cast state and poor plasticity in hot rolling are uncontrollable, making it difficult to achieve large-scale stable industrial production. 5) The annealing process parameters of cold plates are not compatible with the boron microalloying system. If the temperature is too high, the grains coarsen and boron grain boundaries segregate and are lost. If the temperature is too low, recrystallization is incomplete, and the improvement of forming performance is limited. Summary of the Invention
[0004] To address the shortcomings in the aforementioned boron microalloying process for improving chromium ferritic stainless steel, this invention provides a method for manufacturing boron microalloyed chromium ferritic stainless steel. Through innovative synergistic optimization of refining, hot rolling, hot wire pickling, cold rolling, and finished product annealing and pickling processes, it provides a complete manufacturing process for boron microalloyed 430 stainless steel that can be stably produced on a large industrial scale. This effectively improves the cold forming performance of 430 stainless steel and provides a solution for expanding the application of 430 stainless steel in the field of deep-drawing products.
[0005] This invention provides a method for manufacturing boron-microalloyed chromium ferritic stainless steel. By designing the composition of boron-microalloyed 430 ferritic stainless steel, the boron mass content is precisely controlled within the range of 0.005% to 0.01%. The boron alloying process in the refining stage, the hot rolling low-temperature heating process, and the cold rolling process are optimized, resulting in a significant improvement in its formability. The finished product has an r-value ≥ 1.3 (r-value is the planar plastic strain ratio), an elongation after fracture of over 35%, and a planar anisotropy Δr ≤ 0.4, effectively reducing the stamping cracking problem of conventional 430 stainless steel deep-drawn parts.
[0006] The boron microalloyed chromium ferritic stainless steel provided by this invention has the following chemical composition by mass percentage: C: 0.025%–0.045%; Si: 0.20%–0.50%; Mn: 0.20%–0.50%; P: <0.025%; S: <0.015%; Cr: 16.0%–17.0%; N: 0.020%–0.030%; B: 0.005%–0.01%, B / N (mass ratio) = 0.15–0.35; the remainder being Fe.
[0007] The above-mentioned method for manufacturing chromium ferritic stainless steel in boron microalloying specifically includes the following steps: (1) The boron content is controlled within a specific narrow range, with a mass percentage of B of 0.005 to 0.01% and a B / N (mass ratio) of 0.15 to 0.35. This balances the forming performance with the plasticity of hot and cold working, and is different from high-boron neutron-absorbing stainless steel. (2) LF refining step deoxidation sequence control process: aluminum deoxidation is performed first, and boron iron wire is fed at the end of refining to eliminate brittle inclusions of BN and B2O3 from the source and stabilize the boron element yield. (3) During the hot rolling process, the heating temperature of the heating furnace is controlled at 1100~1130℃, the roughing mill exit temperature is 1000~1020℃, and the finishing mill exit temperature is 830~880℃. The hot rolling process achieves low temperature control, eliminates the segregation of cast boron, and avoids the precipitation of intergranular borides during high-temperature rolling. (4) The continuous annealing process employs low-temperature annealing combined with a large cold rolling reduction rate, achieving directional control of the texture and improving the forming performance of the cold-rolled sheet. This invention differs from bell-type annealing by using a hot-wire continuous annealing process.
[0008] The equipment used in the production process of this invention is the same as that used in conventional processes, and the specific steps are as follows: 1) Smelting: Electric arc furnace + AOD + LF process After melting scrap steel and high-carbon ferrochrome in an electric arc furnace, the molten steel is transferred to an AOD furnace, where the carbon content (C) is precisely controlled to be ≤0.04%. After decarburization, the steel is fed into an LF refining furnace. Al is first added for strong deoxidation to reduce free oxygen in the steel. Then, a small amount of ferrotitanium is added to fix the free nitrogen in the molten steel, preferentially generating stable TiN and preventing the subsequent combination of boron and nitrogen to form hard BN inclusions. The LF refining process is heated to 1520–1550℃, and the temperature and composition of the molten steel are finely adjusted. 5–10 minutes before tapping, ferroboron alloy wire is fed in. After feeding the wire, argon gas is used for bottom blowing and stirring for 3–5 minutes to uniformly distribute the boron in the steel and stabilize the boron recovery rate at ≥75%. 2) Continuous casting: electromagnetic stirring + billet holding The casting process employs a fully oxidation-free protection method using an immersion nozzle and a mold mold protective slag, reducing secondary oxidation of the molten steel during casting. Electromagnetic stirring is used to ensure an equiaxed crystal ratio of ≥50%, and a constant low casting speed (0.95~1.10m / min) is used to weaken boron solidification segregation. After exiting the mold, the billet is immediately sent to a sealed, slow-cooling furnace under an insulation cover or directly charged into a hot-heating furnace, with a billet surface temperature ≥650℃. This inhibits the enrichment of boron between dendrites, significantly reduces macroscopic and central boron segregation, and narrows the range of uneven composition in the billet.
[0009] 3) Hot rolling process Slab heating temperature: 1100~1130℃, holding time 7~9min / mm, roughing mill exit temperature: 1000~1020℃, finishing mill exit temperature: 850~880℃, coiling temperature: 610~630℃. Low temperature control is adopted throughout the hot rolling line to suppress the precipitation of borides along the crystal during the cooling process.
[0010] 4) Hot wire annealing and pickling Hot-wire annealing temperature: 840–880℃; hot-wire scale breaking elongation control range: 1.0%–2.0%; shot blasting speed control range: 2000–2300 rpm; pickling speed: 50–60 m / min; pickling temperature: 80–100℃; sulfuric acid concentration: 280–350 g / L; nitric acid concentration: 130–150 g / L; hydrofluoric acid concentration control range: 2–7 g / L. The above three acids are used in combination during the pickling process.
[0011] 5) Cold rolling The total reduction rate of cold rolling is 75% to 85%, which provides sufficient deformation storage energy for the recrystallization annealing of the finished product and improves the recrystallization ability of the material at low temperatures.
[0012] 6) Finished product annealing and pickling The annealing temperature is 810–840℃, the annealing rate is 50–60 m / min; the concentration of electrolytic sodium sulfate is 2.0–2.5 g / L, the concentration of nitric acid is 200–220 g / L, the pickling temperature is 40–80℃, and after annealing and pickling, the temperature is cooled to below 400℃ at a rate of 20–30℃ / min to fully utilize the segregation effect of boron grain boundaries and optimize the deep drawing texture.
[0013] The beneficial effects of this invention are: (1) By adopting the manufacturing method of the present invention, on the basis of the existing 430 production system, no new core equipment is required, the forming performance of 430 ferritic stainless steel is significantly improved, the material elongation is increased to more than 35%, the r value is increased to more than 1.3, Δr≤0.40, and the deep drawing performance is significantly improved. (2) The present invention maintains both material economy and production process feasibility. While improving the material forming performance, it also has a certain effect on corrosion resistance. It is suitable for the production of ferritic stainless steel thin plates for high-end deep-drawing home appliances and decorative panels. Detailed Implementation
[0014] The present invention will be further illustrated by the following embodiments, but is not limited to the following embodiments. Example 1
[0015] The chemical composition of 430 ferritic stainless steel coil, by weight percentage, contains the following components: C: 0.035%; Si: 0.34%; Mn: 0.32%; P: 0.023%; S: 0.001%; Cr: 16.2%; N: 0.024%; B: 0.008%; B / N: 0.33, with the remainder being Fe.
[0016] Step 1: EAF+AOD+LF smelting, LF refining temperature is raised to 1545℃, ferroboron alloy wire is fed in 8 minutes before tapping, after the wire feeding is completed, argon gas bottom blowing and stirring is carried out for 5 minutes, the casting speed is 1.10m / min during continuous casting, the equiaxed crystal ratio of the billet is 53%, and the billet is immediately sent into the heat preservation cover for slow cooling after exiting the crystallizer to obtain a continuous casting billet with a thickness of 200mm.
[0017] Step 2: Hot rolling furnace temperature: 670℃, heating temperature: 1110℃, holding time: 180min, roughing mill exit temperature: 1000℃, finishing mill exit temperature: 860℃, coiling temperature: 620℃, producing a hot-rolled coil with a thickness of 3.5mm.
[0018] Step 3: Hot wire annealing temperature: 850℃, hot wire scale breaking elongation: 1.5%, shot blasting speed: 2000 rpm, pickling speed: 55 m / min, acid temperature: 80℃, sulfuric acid concentration: 280 g / L, nitric acid concentration: 130 g / L, hydrofluoric acid concentration control range: 7 g / L.
[0019] Step 4: Cold rolling total reduction rate 78%, annealing temperature 830℃, annealing rate: 50 / min; electrolytic sodium sulfate concentration: 2.5g / L, nitric acid concentration: 220g / L, pickling temperature 80℃. After annealing and pickling, cool to 350℃ at a rate of 30℃ / min to produce a finished cold plate with a thickness of 0.78mm.
[0020] The finished cold-rolled sheet obtained by using this invention has a yield strength of 316 MPa, a tensile strength of 499 MPa, an elongation of 37%, and an r-value of 1.41, exhibiting excellent deep-drawing performance.
[0021] Example 2
[0022] The chemical composition of 430 ferritic stainless steel coil, by weight percentage, contains: C: 0.042%; Si: 0.35%; Mn: 0.33%; P: 0.018%; S: 0.001%; Cr: 16.5%; N: 0.027%; B: 0.005%; B / N: 0.18, with the remainder being Fe.
[0023] Step 1: EAF+AOD+LF smelting, LF refining temperature is raised to 1545℃, ferroboron alloy wire is fed in 8 minutes before tapping, after the wire feeding is completed, argon gas bottom blowing and stirring is carried out for 5 minutes, the casting speed is 1.09m / min during continuous casting, the equiaxed crystal ratio of the billet is 55%, and the billet is immediately sent into the heat preservation cover for slow cooling after exiting the crystallizer to obtain a continuous casting billet with a thickness of 200mm.
[0024] Step 2: Hot rolling furnace temperature: 658℃, heating temperature: 1110℃, holding time: 180min / mm, roughing mill exit temperature: 1000℃, finishing mill exit temperature: 850℃, coiling temperature: 630℃, producing a hot-rolled coil with a thickness of 4.5mm.
[0025] Step 3: Hot wire annealing temperature: 860℃, hot wire scale breaking elongation: 1.8%, shot blasting speed: 2000 rpm, pickling speed: 60 rpm, acid temperature: 75℃, sulfuric acid concentration: 340 g / L, nitric acid concentration: 130 g / L, hydrofluoric acid concentration control range is 6 g / L.
[0026] Step 4: Cold rolling total reduction rate 82%, annealing temperature 820℃, annealing rate: 60 / min; electrolytic sodium sulfate concentration: 2.5g / L, nitric acid concentration: 220g / L, pickling temperature 80℃. After annealing and pickling, cool to 380℃ at a rate of 30℃ / min to produce a finished cold plate with a thickness of 0.81mm.
[0027] The finished cold-rolled sheet obtained by using this invention has a yield strength of 330 MPa, a tensile strength of 522 MPa, an elongation of 35%, and an r-value of 1.31, and also has excellent deep-drawing performance.
[0028] Comparative Example 1 The chemical composition of 430 ferritic stainless steel coil without boron is as follows by weight percentage: C: 0.037%; Si: 0.30%; Mn: 0.36%; P: 0.025%; S: 0.001%; Cr: 16.3%; N: 0.035%; with the remainder being Fe.
[0029] Step 1: AOD+LF smelting, LF refining and heating to 1555℃, continuous casting process with a casting speed of 1.10m / min, equiaxed crystal ratio of 53% for the billet, the billet is immediately sent into a heat insulation cover for slow cooling after exiting the crystallizer, and a continuous casting billet with a thickness of 200mm is obtained.
[0030] Step 2: Hot rolling furnace temperature: 90℃, heating temperature: 1150℃, holding time: 180min / mm, roughing mill exit temperature: 1030℃, finishing mill exit temperature: 880℃, coiling temperature: 650℃, producing a hot-rolled coil with a thickness of 4.5mm.
[0031] Step 3: Hot wire annealing temperature: 850℃, hot wire scale breaking elongation: 1.8%, shot blasting speed: 1800 rpm, pickling speed: 55 m / min, acid temperature: 80℃, sulfuric acid concentration: 250 g / L, nitric acid concentration: 140 g / L, hydrofluoric acid concentration control range: 5 g / L.
[0032] Step 4: Cold rolling total reduction rate 85%, annealing temperature 850℃, annealing speed: 50 / min; electrolytic sodium sulfate concentration: 2.5g / L, nitric acid concentration: 220g / L, pickling temperature 80℃, producing finished cold plate with a thickness of 0.67mm.
[0033] The finished cold-rolled steel sheet produced by this process has a yield strength of 337 MPa, a tensile strength of 505 MPa, an elongation of 28%, an r-value of 0.95, and poor formability.
[0034] Compared with Comparative Example 1, the 430 ferritic stainless steel prepared in Examples 1-2 of the present invention has significantly improved formability, with material elongation increased to over 35%, r-value increased to over 1.3, and deep drawing performance significantly improved.
Claims
1. A boron microalloyed chromium ferritic stainless steel, characterized in that, The chemical composition, by mass percentage, includes: C: 0.025%–0.045%; Si: 0.20%–0.50%; Mn: 0.20%–0.50%; P: <0.025%; S: <0.015%; Cr: 16.0%–17.0%; N: 0.020%–0.030%; B: 0.005%–0.01%, with a B / N mass ratio of 0.15–0.35; the remainder being Fe.
2. A method for manufacturing boron microalloyed chromium ferritic stainless steel according to claim 1, characterized in that... Includes the following: (1) Narrow-range trace boron control: the mass percentage of B is 0.005-0.01%, and the B / N mass ratio is 0.15-0.35; (2) LF refining step deoxidation sequence control process: aluminum deoxidation is performed first, and boron iron wire is fed at the end of refining to eliminate brittle inclusions of BN and B2O3 from the source and stabilize the boron element yield. (3) During the hot rolling process, the heating temperature of the heating furnace is controlled at 1100~1130℃, the roughing mill exit temperature is 1000~1020℃, and the finishing mill exit temperature is 830~880℃. The hot rolling process achieves low temperature control, eliminates the segregation of cast boron, and avoids the precipitation of intergranular borides during high-temperature rolling. (4) The continuous annealing process employs low-temperature annealing combined with cold rolling with a large reduction rate to achieve directional control of the texture and improve the forming performance of the cold-rolled sheet.
3. The method for manufacturing boron microalloyed chromium ferritic stainless steel according to claim 1, characterized in that, Includes the following steps: 1) Smelting: Electric arc furnace + AOD + LF process After melting scrap steel and high-carbon ferrochrome in an electric arc furnace, the molten steel is transferred to an AOD furnace for precise carbon content control. After decarburization, it is fed into an LF refining furnace, where Al is first added for strong deoxidation to reduce free oxygen in the steel. Then, a small amount of ferrotitanium is added to fix the free nitrogen in the molten steel, preferentially generating stable TiN and preventing the subsequent combination of boron and nitrogen to form hard BN inclusions. The LF refining process is heated to 1520-1550℃, and the temperature and composition of the molten steel are finely adjusted. 5-10 minutes before tapping, ferroboron alloy wire is fed in, and after feeding, argon gas is used for bottom blowing and stirring for 3-5 minutes to uniformly distribute boron in the steel, achieving a stable boron recovery rate of ≥75%. 2) Continuous casting: electromagnetic stirring + billet holding The entire process of casting is oxidation-free by using an immersion nozzle and a mold protective slag to reduce secondary oxidation of molten steel during casting. Electromagnetic stirring is used to ensure an equiaxed crystal ratio of ≥50%, and constant low casting speed weakens boron solidification segregation. After exiting the mold, the billet is immediately sent to a heat-insulating cover for slow cooling or directly charged into a hot furnace. The surface temperature of the billet is ≥650℃, which inhibits the enrichment of boron between dendrites, significantly reduces macroscopic and central boron segregation, and narrows the range of uneven composition in the billet. 3) Hot rolling process Slab heating temperature: 1100~1130℃, holding time 7~9min / mm, roughing mill exit temperature: 1000~1020℃, finishing mill exit temperature: 850~880℃, coiling temperature: 610~630℃. Low temperature control is adopted throughout the hot rolling line to suppress the precipitation of borides along the crystal during the cooling process. 4) Hot wire annealing and pickling Hot wire annealing temperature: 840~880℃, hot wire scale breaking elongation control range: 1.0%~2.0%, shot blasting speed control range: 2000~2300 rpm, pickling speed: 50~60m / min, pickling temperature: 80~100℃, sulfuric acid, nitric acid and hydrofluoric acid are used in the pickling process; 5) Cold rolling The total reduction rate of cold rolling is 75% to 85%, which provides sufficient deformation storage energy for the recrystallization annealing of the finished product. 6) Finished product annealing and pickling The annealing temperature is 810–840℃, the annealing rate is 50–60 m / min; the concentration of electrolytic sodium sulfate is 2.0–2.5 g / L, the concentration of nitric acid is 200–220 g / L, the pickling temperature is 40–80℃, and after annealing and pickling, the temperature is cooled to below 400℃ at a rate of 20–30℃ / min to fully utilize the segregation effect of boron grain boundaries and optimize the deep drawing texture.
4. The method for manufacturing boron microalloyed chromium ferritic stainless steel according to claim 3, characterized in that, In step 2), the pulling speed is 0.95 to 1.10 m / min.
5. The method for manufacturing boron microalloyed chromium ferritic stainless steel according to claim 3, characterized in that, Step 4) In the hot wire annealing and pickling, the sulfuric acid concentration is 280-350 g / L, the nitric acid concentration is 130-150 g / L, and the hydrofluoric acid concentration is 2-7 g / L.
6. The method for manufacturing boron microalloyed chromium ferritic stainless steel according to claim 3, characterized in that, The resulting medium-chromium ferritic stainless steel has an r-value ≥ 1.3, an elongation after fracture of over 35%, and Δr ≤ 0.4.